The Effect of Group Cohesion, Loyalty, Leadership on The Quality of Organizational Decision Making: Literature Review - Yohannes Vemberi; Nur Wening; Lucia Ika Fitriastuti (Yayasan Riset dan Pengembangan Intelektual, 2024)
The quality of management decision-making plays a vital role in determining company strategy and achieving company performance. There are various factors that may affect the quality of management decision-making such as group cohesion, loyalty, and leadership will be discussed in this article. This article aims to review and present a structured overview of the most recent studies concerning group cohesion, loyalty, leadership, and decision making quality. It delves into an analysis of relevant studies published between 2014-2022. This article analyzes previous research through the perspective of employed research methodologies, research findings, and a critical review. The analysis results of this article would bring problems’ alternative, research topic ideas and opportunities for further research related to group cohesion, loyalty, leadership, and decision-making quality. The implication of this research for practitioners or managers is to increase information and knowledge about various factors that must be considered in order to make quality decisions.